Anterior lumbar interbody fusion with a novel osteoinductive allograft – Mid-term clinical and radiographic outcomes - Charlie R. Faulks; Dean T. Biddau; Michael D. Selby; Ralph J. Mobbs; Gregory M. Malham (World Neurosurgery: X)
Objectives: Graft material can impact fusion rates in anterior lumbar interbody fusion (ALIF) procedures. We aimed to evaluate the clinical and radiographic outcomes of patients who underwent ALIF with a novel osteoinductive demineralised bone allograft (DBA) due to the paucity of peer reviewed literature. Methods: Includes 112 consecutive patients from 3 senior spine surgeons (multi-centre) undergoing stand-alone ALIF with osteoinductive DBA (Allovance® Crunch Plus) between January 1, 2019 and January 1, 2022. Patient reported outcome measures included visual analog scale (VAS) back pain, Oswestry disability index (ODI) and 12-Item Short Form Survey (SF-12) measured at preoperative, 6-week, 6-month, 12-month, and 24-month time points. CT imaging conducted postoperative day-2 for instrumentation positioning then at either 6-, 12- or 24-months for interbody fusion status. If fusion was achieved no further CTs were undertaken. Minimum follow-up was 12 months (12–24). Results: Mean age of cohort (51.8 % male) was 51.4 ± 14.1 years. Procedures consisted of; single level (n = 71), double level (n = 20), or quadruple level (n = 2) ALIF, and hybrid procedures (n = 19, disc replacement superior to ALIF). Preoperative mean VAS back (7.5 ± 1.5), and ODI (30.4 ± 7.8) significantly (p < 0.0001) decreased (2.5 ± 2.1, 12.2 ± 8.1); SF-12 physical (29.4 ± 5.7), and SF-12 mental (41.3 ± 12.2) showed improvements (p < 0.05) at 12-months follow-up (47.5 ± 8.8, 52.6 ± 7.6). Fusion was achieved at 6-months in 23.6 %, 12-months in 86.8 %, and 24-months in 93.4 % of patients. Nineteen (30.6 %) patients suffered acute (n = 8) and chronic (>6 months, n = 11) complications. Conclusions: Patients undergoing ALIF with this novel osteoinductive DBA demonstrated significant improvement in pain, disability and function with high fusion rates over 24-month follow-up.